If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12(4x-5)=-11(10x+10)+208
We move all terms to the left:
12(4x-5)-(-11(10x+10)+208)=0
We multiply parentheses
48x-(-11(10x+10)+208)-60=0
We calculate terms in parentheses: -(-11(10x+10)+208), so:We get rid of parentheses
-11(10x+10)+208
We multiply parentheses
-110x-110+208
We add all the numbers together, and all the variables
-110x+98
Back to the equation:
-(-110x+98)
48x+110x-98-60=0
We add all the numbers together, and all the variables
158x-158=0
We move all terms containing x to the left, all other terms to the right
158x=158
x=158/158
x=1
| 7(x+6)=54+6x | | 4*(x+7)=-7*(x+9)+124 | | x÷7=9 | | 8*(x+10)=-10*(x-4)+4 | | 3x-16=34 | | (x+8)=15x+3 | | x9=115 | | 2x+11=5x-13x | | /2+3x5=35 | | x^2-9x+4x-36=0 | | 3x+12=10–2x | | 3z/10-5=0 | | 12-2v=5v+5 | | 4-x/10=9 | | -4x-5=3-x | | 10x-6=-8 | | 12x-6-x+2=8x+4 | | 8*(x-11)=-11*(x-3)-273 | | 15+5•(5+3x)=70 | | 10z-1=1 | | 11*(3x-6)-4*(10x-7)=-87 | | 2s=2+s.s | | 7−x/8=6 | | 10*(10x+3)+6*(2x-6)=-6 | | 2(2x+5)7=3x−46+53 | | 4x^2-15x+9=-6x+4 | | 4*(6x-11)+6*(7x+5)=-14 | | 5s*44=134 | | 6a+3=7-4a | | x^2+13x-31=6x-1 | | 0=e.e-19e+32 | | x^2+13x-31=6x+1 |